Diskriminasi Sosial Dalam Novel A Wrinkle in Time Karya Madeleine L’engle - Siti Fauziah, Diba (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research aims to describe the depiction of social discrimination in the novel A Wrinkle In Time by Madeliene L'Engle from the conflict experienced by the main character. The method used in this research is a descriptive qualitative and objective approach, with data collection methods of listening, reading and observing. The discrimination depicted in the novel A Wrinkle In Time includes direct discrimination and indirect discrimination. The results of this research describe social discrimination and its influence on changes in the personalities of Meg Murry and Charles Wallace.